2006
DOI: 10.1152/ajpregu.00738.2005
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and neuroendocrine responses to changes in sodium intake in compensated heart failure

Abstract: neuroendocrine responses to changes in sodium intake in compensated heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 30 publications
(31 reference statements)
7
76
1
1
Order By: Relevance
“…Decreased pulmonary artery and capillary wedge pressures without change in cardiac index and systemic vascular resistance was observed by Cody and colleagues 33 in New York Heart Association (NYHA) class III to IV patients with a very low sodium diet, but Damgaard and colleagues 34 noted a decrease in cardiac index and stroke volume and an increase in pulmonary vascular resistance with a low-sodium diet in NYHA class II to III patients. Two studies by Volpe and colleagues 35,36 concluded that moderate-to-high sodium intake had no hemodynamic effects on NYHA I to II patients Only consensus opinion of experts, case studies, or standard of care; FairϭBenefits exceed the harms but quality of evidence is not as strong; 1ϩ ϭ well-conducted meta-analysis, systemic reviews, or randomized controlled trials with low risk of bias.…”
Section: Physiological and Neurohormonal Responsesmentioning
confidence: 93%
“…Decreased pulmonary artery and capillary wedge pressures without change in cardiac index and systemic vascular resistance was observed by Cody and colleagues 33 in New York Heart Association (NYHA) class III to IV patients with a very low sodium diet, but Damgaard and colleagues 34 noted a decrease in cardiac index and stroke volume and an increase in pulmonary vascular resistance with a low-sodium diet in NYHA class II to III patients. Two studies by Volpe and colleagues 35,36 concluded that moderate-to-high sodium intake had no hemodynamic effects on NYHA I to II patients Only consensus opinion of experts, case studies, or standard of care; FairϭBenefits exceed the harms but quality of evidence is not as strong; 1ϩ ϭ well-conducted meta-analysis, systemic reviews, or randomized controlled trials with low risk of bias.…”
Section: Physiological and Neurohormonal Responsesmentioning
confidence: 93%
“…In a previous study, Damgaard et al [15] addressed the adaptation of sodium excretion after an abrupt change in salt intake in both directions. Twelve healthy male subjects were submitted in a randomized order to 2 levels of salt intake (70 and 250 mmol/day; study F).…”
Section: U Na and V After An Abrupt Change In Sodium Intakementioning
confidence: 99%
“…Fluid intake was ad libitum. Their article showed how daily sodium excretion (U Na V) adapted, day after day, to these abrupt switches in salt intake [15], but U Na and V were not reported. Figure 2 shows these 2 variables along with the previously published U Na V. It appears clearly that V remained fairly constant over the whole period of observation in spite of marked changes in sodium excretion.…”
Section: U Na and V After An Abrupt Change In Sodium Intakementioning
confidence: 99%
“…19 Similarly, a more recent therapeutic approach comprising high-dose oral furosemide and higher daily Na intake associated with fluid restriction has been reported to portend beneficial effects with very promising results in chronic HF patients; it is also likely to lower the incidence of hyponatremia in this patient population. [23][24][25][26] Vasopressin receptor antagonists (VRA), also called aquaretics or vaptans, represent the emerging strategy for treatment of HF-associated hyponatremia. Three types of vasopressin receptors have been identified with distinct functions: V1a, V1b, and V2.…”
Section: Newer Management Strategymentioning
confidence: 99%